2008
DOI: 10.1016/j.combustflame.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and numerical investigation on the influence of external gas recirculation on the HCCI autoignition process in an engine: Thermal, diluting, and chemical effects

Abstract: In order to contribute to the solution of controlling the auto-ignition in a Homogeneous Charge Compression Ignition (HCCI) engine, parameters linked to External Gas Recirculation (EGR) seem to be of particular interest. Experiments performed with EGR present some difficulties in interpreting results using only the diluting and thermal aspect of EGR. Lately, the chemical aspect of EGR is taken more into consideration, because this aspect causes a complex interaction with the dilution and thermal aspects of EGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
(27 reference statements)
3
43
0
Order By: Relevance
“…Therefore, the presence of incomplete combustion products such as carbon monoxide, unburned hydrocarbon and nitrogen oxides play an important role. Results on CO and HC showed no significant effect on the combustion timing while nitric oxide demonstrated a promoting effect [8,38]. Dubreuil et al [39] investigated the nitric oxide effect on reference fuels and observed a promoting effect on both cool and main flames for concentration lower than 100 ppm.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the presence of incomplete combustion products such as carbon monoxide, unburned hydrocarbon and nitrogen oxides play an important role. Results on CO and HC showed no significant effect on the combustion timing while nitric oxide demonstrated a promoting effect [8,38]. Dubreuil et al [39] investigated the nitric oxide effect on reference fuels and observed a promoting effect on both cool and main flames for concentration lower than 100 ppm.…”
Section: Introductionmentioning
confidence: 95%
“…To alleviate this stated problem, mixture composition should be formed to have different ignition timings depending on its position in the cylinder. Machrafi et al described the effect on ignition timing and heat release rate of NO, CO, CH 2 O in EGR of the previous cycle [2]. Shi et al reported a phenomenon that the peak pressure of a cycle in the cylinder decreases as EGR portion increases [3].…”
Section: Introductionmentioning
confidence: 97%
“…The main obstacles in the homogeneous charge compression ignition (HCCI) engine combustion are its timing control and narrow operation range [1][2][3][4][5][6]. Unlike spark ignition (SI) and compression ignition (CI) combustion modes, whose combustion phasing can be controlled by the timing of spark and fuel injection, respectively, HCCI combustion is an auto-ignition process controlled by a chemical reaction, which, in itself, is difficult to handle.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EGR gases have the following important properties for controlling HCCI combustion: ① Its internal energy can be directly used to adjust in-cylinder gas temperature; ② EGR will change the heat capacity ratio of in-cylinder mixtures, thus temperature history will also change (especially, in compression stroke). The dilution of its inert components may also reduce the chemical reaction rate; and ③ There are some active species in EGR gases (especially when the combustion efficiency of the previous cycle is low), which, although small in amount, may have great influence on the combustion process of the next cycle [1,2].…”
Section: Introductionmentioning
confidence: 99%